ANALYSIS OF MATHEMATICAL MODELS OF UNSTABLE WATER MOVEMENT IN WATER ECONOMY FACILITIES TAKING INTO ACCOUNT THE MULTI-DIMENSIONAL DISTRIBUTION OF PARAMETERS IN SPACE (Conferencea, 2023)
The article describes the analysis of the mathematical models of unstable water movement in water management facilities, taking into account the multidimensional distribution of parameters in space.